RESPONSE OF GROWTH TRAITS AND GRAIN YIELD OF Zea mays L. TO SPRAY BY PROLINE AND ARGININE - Dawood, Wisam Malik; Glaim, Azhar Amer (Diyala Agricultural Sciences Journal, 2018)
This study was carried out in according to randomized complete block design (RCBD) in the field of Baquba nursery belong to Diyala Directorate, during autumn season of 2015. The aim of study was to determine the effect of proline and arginine on the traits of vegetative growth and corn grain yield using the following treatments, without spraying (control treatment) and spraying with distilled water and spraying proline and arginine amino acids at the concentrations of 100 and 200 mg l-1. The experiment was conducted at three replicates. After planting, all the treatments were applied, then the studied traits were calculated. At the maturity stage the data was collected and analyzed, then the means of traits were compared with each other using less significant difference (LSD). The results showed that spraying proline at a concentration of 200 mg l-1, led to a significant increase in the traits were chlorophyll guide, number of leaves, leaf area, plant height and yield grains per plant amounted to 15.34, 27.13, 14.8, 14.60 and 17.35% respectively. The results also showed superiority of using 200 mg l-1, arginine morally to give the highest increase in the above mentioned traits which were 10.17, 18.73, 10.57, 8.27 and 16.35 %, respectively.